THE DILEMATIC ON-LINE ENGLISH LEARNING DURING THE COVID-19 PANDEMY IN RURAL AREA - Moh Hafidz (Universitas Lambung Mangkurat, 2020)
Abstract: The government has made a decision of COVID-19 pandemic through the Minister of Education and Culture Circular No. 4 dated 24 March 2010 concerning the Implementation of Education Policy in the Emergency Period of Corona Virus Disease (COVID-19), namely learning from home. The problems are English language skills and students’ motivation. This study aims to describe English language skills and student motivation during the COVID-19 pandemic. The benefit is facilitating lecturers in online learning based on appropriate applications with students are in the rural area. This study uses a qualitative descriptive method by conducting the Monkey Survey application to collect and analyse data, it created and applied on May 29, 2020 and closed on May 31, 2020. After May 31, 2020 respondents could not open and fill out the questionnaire because the closed Application. The sample of this study was 35 students who studied English online by using different applications. The category is the education category and this application was modified on June 2, 2020. The result of his research is that online English Learning research during the COVID-19 pandemic is that the use of the WhatsApp, Facebook, YouTube and Google Classroom applications improve writing, listening and speaking skills and have no effect on reading skill, because reading skills can be improved by using the Schoology application. While the Schoology application cannot be used because of internet network limitations and quotas. Other findings are that online English language learning during the COVID-19 pandemic cannot increase student motivation.